Validity and Reliability of a Physical Fitness Test Instrument for Physical Education Students - Hendrik; Karo Karo, Alan Alfiansyah Putra; Sari, Liliana Puspa (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
Examining the validity and reliability of a physical fitness test tool created especially for physical education students was the goal of this study.  To ensure precise evaluation and evidence-driven curriculum development, it is increasingly vital in higher education to utilize standardized and psychometrically robust tools for assessing physical fitness. The study involved 200 physical education students, aged 18 to 23. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were employed to assess the construct validity of the tool, while five specialists utilized the Content Validity Index (CVI) to review its content validity. Cronbach’s alpha was used to evaluate internal consistency, while the Intraclass Correlation Coefficient (ICC) was employed to measure test-retest stability. The findings indicated strong reliability (Cronbach’s alpha = 0.91; ICC = 0.88), solid construct validity with six identified variables (KMO = 0.82; Bartlett’s Test p < 0.001; CFA CFI = 0.94; RMSEA = 0.05), and considerable content validity (CVI = 0.89). These results endorse the standardization of fitness evaluation tools and offer valuable insights for educators, researchers, and coaches in higher education, demonstrating that the tool is valid, reliable, and suitable for both academic research and practical use.